A fix to modeled biases in rainfall microphysical process rates. (11th June 2013) - Schultz, Colin
Abstract : Much of the uncertainty in global climate models stems from issues involved in accurately representing cloud properties. The difficulty arises in parameterizing the small‐scale physical interactions that turn water vapor to cloud to rain.